Atp Induces Il-1 Beta Secretion in Neisseria Gonorrhoeae-Infected Human Macrophages by a Mechanism Not Related to the Nlrp3/Asc/Caspase-1 Axis - Acuna-Castillo, C (HINDAWI PUBLISHING CORP, 2016)
Neisseria gonorrhoeae (Ngo) has developed multiple immune evasion mechanisms involving the innate and adaptive immune responses. Recent findings have reported that Ngo reduces the IL-1 beta secretion of infected human monocyte-derived macrophages (MDM). Here, we investigate the role of adenosine triphosphate (ATP) in production and release of IL-1 beta in Ngo-infected MDM. We found that the exposure of Ngo-infected MDM to ATP increases IL-1 beta levels about ten times compared with unexposed Ngo-infected MDM (P < 0.01). However, we did not observe any changes in inflammasome transcriptional activation of speck-like protein containing a caspase recruitment domain (CARD) (ASC, P > 0.05) and caspase-1 (CASP1, P > 0.05). In addition, ATP was not able to modify caspase-1 activity in Ngo-infected MDM but was able to increase pyroptosis (P > 0.01). Notably ATP treatment defined an increase of positive staining for IL-1 beta with a distinctive intracellular pattern of distribution. Collectively, these data demonstrate that ATP induces IL-1 beta secretion by a mechanism not related to the NLRP3/ASC/caspase-1 axis and likely is acting at the level of vesicle trafficking or pore formation.